2018
DOI: 10.9789/2175-5361.2018.v10i3.801-809
|View full text |Cite
|
Sign up to set email alerts
|

Incontinence-Associated Dermatitis in Hospitalized Elderly Patients: Nurses’ Self-Reported Knowledge / Dermatite Associada à Incontinência em Idosos Hospitalizados: Conhecimento Autorreferido de Enfermeiros

Abstract: Objetivo: Identificar o conhecimento autorreferido dos enfermeiros em relação a prevenção, diagnóstico e tratamento da dermatite associada a incontinência (DAI) em idosos hospitalizados e propor a construção de um protocolo de cuidados de enfermagem a partir de fluxograma. Métodos: Pesquisa exploratória descritiva, qualitativa, através de entrevista semiestruturada com enfermeiros de unidades de um hospital, no segundo semestre de 2016. Os dados das entrevistas foram analisados mediante análise temática. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 5 publications
(5 reference statements)
1
7
0
7
Order By: Relevance
“…Nutrition is an important determinant in the prognosis of patients at high risk for developing skin lesions, as well as a fundamental part of their healing process (6,24) . The present study evidenced the association between enteral diet and IAD, corroborating a research-correction of a historical hospital cohort (21) , which aimed to estimate survival and verify factors associated with IAD in critically ill patients at a public hospital: it was evidenced that the risk of bacterial contamination, high osmolarity and lack of fiber related to enteral tube feeding (10,25) favor the establishment of diarrhea, which is considered an important factor for the formation of IAD (26) .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Nutrition is an important determinant in the prognosis of patients at high risk for developing skin lesions, as well as a fundamental part of their healing process (6,24) . The present study evidenced the association between enteral diet and IAD, corroborating a research-correction of a historical hospital cohort (21) , which aimed to estimate survival and verify factors associated with IAD in critically ill patients at a public hospital: it was evidenced that the risk of bacterial contamination, high osmolarity and lack of fiber related to enteral tube feeding (10,25) favor the establishment of diarrhea, which is considered an important factor for the formation of IAD (26) .…”
Section: Discussionsupporting
confidence: 86%
“…Authors emphasize that skin tissue tolerance and health condition (1,10) , cognitive and nutritional conditions (6) , mechanical friction (6,11) , use of diapers (10,12) and inadequate genital hygiene (12) , use of medications (11) are contributing factors for lesions associated with incontinence or moisture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, it is reported that nurses should improve their professional knowledge about the prevention and management of IAD. 23,34,38,39 Studies on the prevalence of IAD in ICUs are limited; however, 2 studies showed an IAD prevalence ranging from 5% to 17% in the ICU setting. 9,11 The wide range in prevalence rates may be due to the critical condition of the patients, incontinence, the clinical setting, different skin types and characteristics, and methodological differences between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Porém, sabe-se que o AGE não é capaz de formar uma camada protetora na pele, sendo facilmente removido ao entrar em contato com a fralda. Além disso, produtos oclusivos não são indicados para estas lesões, assim, o AGE não deve ser utilizado para a DAI 1,23 .…”
Section: Avaliaçãounclassified